THE HORIZONS OF COGNITIVE PEDAGOGY - Siemieniecka, Dorota; Siemieniecki, Bronisław (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article addresses the problems of cognitive theory and research relevant to understanding the mechanisms of the learning process. It is meant to define the concept of cognitive pedagogy and emphasise the need for a new genetic/socio/cultural/media perspective, which in turn requires new research tools and increased attention to research results in the field of neuroscience. The authors define and characterise cognitive areas of cognitive pedagogy.